Protection against Government Takings: Compensation for Regulation? - Kevin Guerin (New Zealand Government, The Treasury, 2002)
The paper responds to recent debate in New Zealand on the power of the government to take private property, directly or through regulatory constraints. This aspect of regulation has received less attention in New Zealand than it warrants. This paper addresses the issue of which protections against takings are appropriate, and the role of compensation as a protective device. A taking can be broadly defined an act by which a government assumes or assigns control over all or part of a property right held by a private party. Government regulation is typically not treated as a taking. In practice, compensation is normally required only for physical takings, such as the acquisition of land, and is not available for takings through regulation, such as restricting the right to use land in a particular way. New Zealand has three options for improved protection against takings: a tighter regime for scrutinising the quality of regulation, more restricted takings powers, and extended compensation provisions. The desirability and practicality of a greater role for compensation requires, however, more detailed consideration. The paper aims to stimulate further debate in this area as an aspect of the wider debate on regulatory quality.
Keywords: D23; K11; K32; Q24; 330; Eminent Domain; Compensation; Regulatory Takings; Police Power; Public Works; Land Use